The accidental systems librarian [electronic resource] - Engard, Nicole C., 1979-; Gordon, Rachel Singer (Medford, N.J. : Information Today, c2012)
This new edition of The Accidental Systems Librarian prepares readers to manage the latest library technologies : mobile devices, open source software, social networks, WiFi, ebooks, and much more. Nicole C. Engard's advice on using research, communication, organizational, and bibliographic skills to solve various systems problems is geared to helping both "accidental" and "planned" systems librarians develop the skills they need to succeed and the confidence they need to excel
Systems librarianship 101: defining systems librarianship -- Systems librarianship 102: desktop software you may need to master -- Systems librarianship 103: web applications you may need to master -- Systems librarianship 104: other technical areas you may need to master -- Organization of knowledge--Research techniques-- Networking--Instruction techniques--Independent study -- Administration and management -- Integrated library system migration -- Life lessons
Includes bibliographical references and index
Keywords: Systems librarians; Electronic books